English GGD Teachers’ Voice in the Use of ICT for Teaching English (Barriers and Strategies) - Neni Nurkhamidah (Universitas Veteran Bangun Nusantara, 2020)
Indonesia is an archipelago country with approximately 17.000 islands in one nation. Many cities have been supported with sufficient and appropriate ICT facilities for education but still many schools in rural area are still far from ideal condition. This research aims at finding out the barriers experience by English GGD as teachers that directly deal with this condition in using ICT for teaching English and the strategies they use to face the barriers. By employing qualitative descriptive study, 17 GGD English teachers were involved. Finding showed that infrastructure and facilities are major barriers face by teachers in implementing ICT on their teaching. To keep using ICT in teaching they take some strategies such as use their own personal ICT tools, prepare material when they find electricity or internet connection, utilize English GGD teacher group to share teaching material, use energy saving application in their computer, and borrow ICT tools from the closest school. Researcher hope that this study can be further used by our government, school, and stakeholder to provide solutions to its obstacles in implementing ICT for English teaching in remote and rural area.